Hydroxyethyl Starch Curcumin Enhances Antiproliferative Effect of Curcumin Against HepG2 Cells via Apoptosis and Autophagy Induction - Linhai Jiang; Linhai Jiang; Xiaoliang Cai; Sheng Li; Ying Miao; Xiaoyu Yang; Manbian Lin; Liang Chen; Xiaozheng He; Zuquan Weng (Frontiers Media S.A., 2021)
It is well documented that curcumin (CUR), as a polyphenol molecule originated from turmeric, has many advantages such as antioxidative, anti-inflammatory, neuroprotective, and antitumor effects. However, because of its poor water solubility and low bioavailability, the biomedical applications of CUR are limited. So, in this study, we modified CUR with conjugation to a food-derived hydrophilic hydroxyethyl starch (HES) via an ester linkage to fabricate the amphiphilic conjugate HES-CUR prior to self-assembling into uniform nanoparticles (HES-CUR NPs). And, the results of the 1H NMR spectra and FT-IR spectrum showed successful synthesis of HES-CUR NPs; moreover, the solubility and the drug loading efficiency of CUR were significantly increased. Next, we further explored the differences on the antitumor effects between HES-CUR NPs and CUR in HepG2 cells, and the results of the CCK8-assay and cell counting experiment showed that HES-CUR NPs exhibited a more significant antiproliferative effect than that of CUR in HepG2 cells. And HepG2 cells were more sensitive to apoptosis induced by HES-CUR NPs as evidenced by flow cytometry, increased cytochrome c level, and decreased full length caspase-3 and Bcl-2 protein expressions. Additionally, we found that the efficacy of HES-CUR NPs against HepG2 cells might be related to the enhanced degree of mitochondrial damage (decrease of the mitochondrial membrane potential and ATP) and autophagy (increased levels of Beclin-1 and LC3-II proteins). So, the findings in this study suggest that HES-CUR NPs have a great application potential in antitumor efficacy and play an important role in multiple signal pathways.